Effect of alkaline fusion on muscovite decomposition and the vanadium release mechanism from vanadium shale. Issue 10 (17th October 2018) - Jian, Xingwen; Huang, Jing; Cai, Zhenlei; Zhang, Yimin; Liu, Tao; Liu, Hong
Abstract : In order to figure out the decomposition of muscovite and the release mechanism of vanadium from vanadium shale in the alkaline fusion process, the process of vanadium release and roasting kinetics by alkaline fusion was studied. It was found that the addition of sodium hydroxide made the muscovite convert into the sodium silicate and gehlenite. This process promoted the dissolution of silicon and the destruction of muscovite, which could facilitate the release of vanadium. The kinetic analysis indicated that the controlling step of vanadium transformation reaction is changed from chemical reaction control to diffusion control with the increase of roasting time. Compared to the diffusion controlling step, the vanadium related chemical reaction was completed in the first period. The alkaline fusion reaction enhanced the decomposition of muscovite, which could accelerate the release of vanadium and reduce the dependence on high temperature and time in the roasting process. The apparent activation energies of chemical reaction control and diffusion control were 42.24 kJ mol −1 and −9.553 kJ mol −1, respectively. The kinetic model of vanadium extraction from vanadium shale using alkaline fusion could be finally established.